Virtual in-game objects as property and subject of intellectual property rights: comparative research - Tsyhankou, Siarhei (Riga Graduate School of Law, 2023)
The use of virtual objects in digital environments, especially in games, has become increasingly prevalent in recent years. This thesis explores the legal treatment of virtual in-game objects, examining whether they can be considered as property and whether they qualify for protection under intellectual property law. The author reviews existing legal frameworks and always relevant case law to determine the extent to which in-game objects can be considered as property. Also, the concepts of possession, ownership, and transferability of such objects were examined. At the same time, the thesis examines the extent to which virtual in-game objects can be protected under intellectual property law. It analyses the applicability of intellectual property law to these objects, and considers the challenges that arise in protecting in-game items, particularly in relation to the difficulty of defining and enforcing intellectual property rights in virtual environments.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Intellectual property law; in-game objects; virtual objects